Land‐Sea Contrast of Global Hourly Precipitation Intensity in ERA5: Dominant Role of Convective Precipitation - Pengsheng Li; Xiao‐Feng Li; Jingjing Yu; Song Yang (Geophysical Research Letters)
Abstract Satellite estimation shows that, contrary to daily precipitation intensity whose heavier centers are almost all located over the moisture‐rich oceans, a large portion of the heavier hourly precipitation intensity (HPI) centers are located over the moisture‐limited mainland. However, the direct cause of this inverted land‐sea contrast (ILSC) of HPI is still unclear. We find the ERA5 data generally reproduces the above ILSC pattern, although its heavier HPI centers are generally weaker than CMORPH data. Then we find the distribution of convective precipitation (CP) plays a key role based on ERA5 data. The CP intensity centers match well with that of the hourly total precipitation over land areas, which are generally greater than those over ocean; contrarily, the large‐scale precipitation intensity centers are mainly located in ocean. This study provides important clues for establishing physical interpretations in the future, but further evaluations based on more direct observations are still needed.